ONA TILI VA ADABIYOT FANLARINI INTEGRATSIYALASHGAN HOLDA O'QITISHNING AFZALLIKLARI - Ochilova Nafosat Xayitmurodovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article explores the benefits of integrated teaching of native language and literature. According to the results of the study, an integrated approach will help students develop language skills and literary concepts, improve critical thinking skills and understand interdisciplinary connections. The article discusses the practical application of this approach, its effectiveness and importance in the educational system.